On the crystallinity and durability of ZDDP tribofilm - Ueda,M; Kadiric,A; Spikes,H (Tribology Letters, 2019)
The current trend for using lower-viscosity lubricants with the aim of improving fuel economy of mechanical systems means that machine components are required to operate for longer periods in thin oil film, mixed lubrication conditions, where the risk of surface damage is increased. Consequently, the performance and durability of the tribofilms formed by antiwear additives, and in particular zinc dialkyldithiophosphate (ZDDP), the main antiwear oil additive used in engine oils, has become an increasingly important issue. In this paper, it is confirmed that ZDDP tribofilms are initially relatively easily removed by rubbing but that they become more durable during prolonged rubbing. FIB-TEM analyses at different stages of tribofilm formation show that during the early stages of rubbing only the tribofilm close to the steel substrate is nanocrystalline, while the outer region is amorphous and easily removed. However, after prolonged rubbing all regions of the tribofilm become nanocrystalline and able to withstand rubbing in base oil without being removed. XPS analysis shows that after extended rubbing the outermost polyphosphate structures change from longer-chain structures such as metaphosphate and polyphosphate to shorter-chain structures including orthophosphate. This depolymerization of ZDDP tribofilm from long- to short-chain phosphate and consequent nanocrystallization are driven by heat and shear stress. EDX analysis shows that this conversion is promoted by diffusion of Fe cation into the bulk of the tribofilm. The finding that ZDDP tribofilms evolve during rubbing from a weaker amorphous structure to a more durable nanocrystalline one has important implications in terms of the behaviour of ZDDPs at low concentrations, on non-metallic surfaces and at very high contact pressures, as well as for the development of ZDDP tribofilm, friction and wear models.